How youth football players learn to succeed - Jonker, L.; Huijgen, B. C. H.; Heuvingh, B.; Elferink-Gemser, M. T.; Visscher, C. (Football Psychology - From Theory to Practice, 2019)
Elite youth football players need to develop multiple performance characteristics to be successful, such as physical, technical, tactical, and psychological skills. To become a professional football player, young players need to invest large numbers of training hours over a prolonged period of time to increase their chance of developing a successful career. In this context, self-regulation of learning is supposed to favour learning efficiency. Previous research states that young players with good self-regulatory skills were found to excel over those with poor self-regulatory skills during career development. Self-regulation of learning refers to the extent to which individuals are metacognitively, motivationally, and behaviourally proactive participants in their own learning process. Skills such as reflection and planning (i.e. meta-cognitive skills), but also effort and self-efficacy (i.e. motivational aspects) are part of the self-regulatory process. In this chapter, we give an insight into the career pathway of 525 elite youth football players in Dutch football academies and relate their chances of becoming professional football players to their development of self-regulatory skills.